Pregnancy in patient with congenitally corrected transposition of the great artery and ventricular septal defect without pulmonary stenosis: A case report - Auliya, Faiza Fardha; Bambang Rahardjo; Indrawan, I Wayan Agung (Universitas Brawijaya, 2025)
Background: Transposition of the Great Arteries (TGA) is a congenital heart defect affected by an embryological misalignment between the aorta and pulmonary trunk. Congenitally Corrected Transposition of the Great Arteries (CCTGA) or L-TGA, accounts for less than 1 % of congenital cardiac disease cases. This report presents the case of a pregnant woman with a history of CCTGA who successfully delivered an infant. Case illustration: A 32-year-old woman presented with vaginal bleeding at 30-32 weeks of gestation and a history of CC-TGA. Her medical history included CCTGA, ventricular septal defect (VSD) without pulmonary stenosis, prior molar pregnancy curettage, breech fetal position, moderate acute respiratory distress syndrome (ARDS), and low body mass index (BMI 16.6 kg/m²). She was classified as WHO Cardiac Risk Class IV due to the high risk of maternal mortality. Following corticosteroid administration for fetal lung maturation and multidisciplinary evaluation, a planned cesarean section was performed at 30 weeks. A male infant was delivered, weighing 1,480 grams, measuring 41 cm in length, with Apgar scores of 7 and 9, and a Ballard score of 18. Conclusion: Early risk assessment, multidisciplinary collaboration, and individualized management are pivotal in reducing maternal and fetal morbidity in patients with CC-TGA.